2014
DOI: 10.1088/1475-7516/2014/03/036
|View full text |Cite
|
Sign up to set email alerts
|

Observing remnants by fermions' tunneling

Abstract: Abstract. The standard Hawking formula predicts the complete evaporation of black holes.In this paper, we introduce effects of quantum gravity into fermions' tunneling from ReissnerNordstrom and Kerr black holes. The quantum gravity effects slow down the increase of Hawking temperatures. This property naturally leads to a residue mass in black hole evaporation. The corrected temperatures are affected by the quantum numbers of emitted fermions. Meanwhile, the temperature of the Kerr black hole is a function of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
97
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 54 publications
5
97
0
Order By: Relevance
“…For the noncovariant realization, the deformed Hamilton-Jacobi method incorporated with the GUP was studied in [29][30][31][32][33][34]. There, it has been shown that the corrections to the standard Hawking temperature depend on the masses and angular momentums of the emitted particles in a nontrivial way.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the noncovariant realization, the deformed Hamilton-Jacobi method incorporated with the GUP was studied in [29][30][31][32][33][34]. There, it has been shown that the corrections to the standard Hawking temperature depend on the masses and angular momentums of the emitted particles in a nontrivial way.…”
Section: Discussionmentioning
confidence: 99%
“…There, it has been shown that the corrections to the standard Hawking temperature depend on the masses and angular momentums of the emitted particles in a nontrivial way. In some cases, such corrections could lead to the remnant being left in the evaporation [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After making the dragging coordinate transformation, applying Kerner and Mann's fermion tunneling method and the spacetime's symmetries of the Kerr Gödel black hole, we have resolved the modified Dirac equation proposed by authors in Refs. [28][29][30]. As a result, the revised tunneling probability has been workout, and the corrected tunneling temperature also discovered.…”
Section: Discussionmentioning
confidence: 99%